Citizens’ engagement in smart cities for promoting circular economy. A Knowledge based framework - Caputo Francesco; Prisco Anna; Lettieri Mattia; Crescenzo Michele (ITM Web of Conferences, 2023)
Smart Cities can be considered as one of the most challenging topics within the last decades. Overcoming the well analysed debate about the digital devices and infrastructures needed for supporting the emergence and viability of Smart Cities, the paper aims at investigating how citizens’ engagement in Smart Cities can be used for promoting positive attitudes and behaviours towards Cities Circular Economy (CCE). Building upon a managerial perspective the paper aims at depicting preliminary conceptual reflections about antecedents and conditions able to influence citizens’ engagement in Smart Cities functioning. The paper proposes a Knowledge Management based framework for supporting both policy makers and managers in better understanding on which levels to act for ensuring a participative approach to the definition of a Circular Economy Logic in Smart Cities ecosystems.